Communication literacy in podcast media: An inferential-ostentive discursive pragmatics perspective - Rahardi, R. Kunjana; Noviance, Kristina Marta (BAHASTRA, 2025)
This study describes the pragmatic meanings of phatic communication in podcast media from a discursive pragmatic perspective based on inferential-ostentive intent. The data source comes from seven episodes of the Agak Laen podcast titled "Didn't Get Angry Even After Crashing a Pajero? 'Habib, I'm Just Happy'" featuring Habib Husein Ja'far Al-Hadar and hosts Boris Bokir, Oki Rengga, Bene Dion, and Indra Jegel. Data collection employed the listening method with note-taking techniques, followed by data reduction and classification. Data analysis used the contextual analysis method involving conventional and virtual contexts, with multimodality-based cybertextual context being the most dominant, along with social, societal, situational, and cultural contexts. Research steps included identification, reduction, interpretation, and presentation of data analysis results. The results of this study are: (1) The pragmatic meaning of the phatic communication of greetings, (2) The pragmatic meaning of the phatic communication of jokes, and (3) The pragmatic meaning of the phatic communication of affirmations. Among the total data analyzed, greetings accounted for 41%, jokes for 36%, and affirmations for 23%, indicating that greetings were the most dominant form of phatic communication found in the podcast. The results of this study are believed to be very useful in developing the science of pragmatics, especially integrative pragmatics which is the integration of discursive pragmatics and multimodality in its five dimensions, namely visual, spatial, gestural, aural, and linguistic.